Peter Fidler: from York Factory to the Rocky Mountains - Belyea, Barbara, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2020)
A cartographic survey containing reflections of Peter Fidler, surveyor for the Hudson's Bay Company. Fidler mapped the fur trade route in the Canadian Shield and hunted buffalo with the Piikani nation of the Great Plains. He illuminated the geography, economics, and history of the time and region.--Provided by publisher.
Introduction: Fidler in Context -- First Journal: From York Factory to Buckingham House -- Second Journal: From Buckingham House to the Rocky Mountains -- Notes to the First Journal -- Notes to the Second Journal.
Keywords: Fidler, Peter, 1769-1822 -- Travel -- Northwest, Canadian; Fidler, Peter, 1769-1822 -- Travel -- West (U.S.); Fidler, Peter, 1769-1822 -- Diaries; Fur trade -- Canada -- History; Fur trade -- West (U.S.) -- History; Fur trade -- West (U.S.) -- History; West (U.S.) -- Discovery and exploration -- Early works to 1800; Northwest, Canadian -- Description and travel -- Early works to 1800; West (U.S.) -- Description and travel -- Early works to 1800; Northwest, Canadian -- Surveys; West (U.S.) -- Surveys